Energy storage system for dual energy harvester for wearable or portable devices - Zainal Abidin, Muhammad Aiman (IEEE, 2021)
In this new age of technological advancement, the usage of vibration for harvesters to provide electrical power for devices can be optimized with the implementation of an energy storing system. This research investigates how a dual-energy harvester that consists of piezoelectric and electromagnetic assembly could store the energy it produced so it can be used whenever necessary. The energy storage system is simulated using Simulink MATLAB that uses a half rectifier to rectify the input voltages that also work as a switching circuit using diodes for each output. The output voltage obtained from energy harvester simulations is 7.55 V and 2.92 V for piezoelectric and electromagnetic respectively. Two types of input with various levels of input (high and/or low) were tested for this energy storage system. It takes 52 minutes for the designed energy storage system to be fully charged from the dual-energy harvester. This outcome from this project provides a possibility for the dual-energy harvester to optimally store a power supply that can be used daily in portable or wearable devices.